Kimura’s Disease Presenting As Scrotal Mass: A Difficult Diagnosis - Xie, Deng Piao; Xu, Yan Fang; Li, Ming Quan (Urology Journal, 2018)
Herein we report a case of Kimura’s disease with unusual manifestations. A 46-year- old Chinese man presented with mass in scrotum which gradually increased in size for approximately 7 years. A computerized tomographic scan of abdomen revealed a soft-tissue density shadow in scrotum and enlargement of lymph nodes in groin and retroperitoneum. The scrotal mass was excised and the biopsy specimen revealed angiolymphoid hyperplasia with infiltration of eosinophils. In conclusion, clinical doctors should pay attention that the patient with eosinophilia and scrotal mass could be indicative for Kimura’s disease.